SISTEM CERDAS DIAGNOSA PENYAKIT KULIT YANG UMUM DI INDONESIA BERBASIS WEB - Suryani, Nining (LPPM Universitas Nusa Mandiri, 2015)
Utilization of computers with the technology-based knowledge, facts, and reasoning can be an alternative solution of consultation and solutions to gain knowledge about a common skin disease that occurs in Indonesia. Skin is the outer organ and a first protective organ in the body. So if there is something happens in the first time that the skin is affected first. In the case of skin diseases in the body, we would entrust to a specialist or expert who already knows more about health. Constraints that often occur between physician specialists or experts who will consult with the patient and the treatment of them are limited the practice of working hours in hospitals or health centers make the queue buildup patients who want treatment so that patients often have to wait in a long queue, limited physician specialists or experts practicing in the off hours of practice at home or in other places as well as the distance and location of the hospital or clinic or other practices to make the treatment of skin diseases is quite costly. This research method uses waterfall SDLC models consisting of analysis, design, coding, and testing. This common skin disease diagnosis intelligent systems is a web-based application web-based consultation that will help the general public to consult and obtain alternative solutions as a recommendation or an opinion in early to know the cause of skin disease that attacks the body as well as how to overcome the problem of skin disease.